Assessment of Air pollution trend in Medan city - Arief Wibowo Suryo; Hendri Irwandi (Jurnal Meteorologi dan Geofisika, 2018)
Medan, as the capital city of the North Sumatra province as well as one of largest metropolitan areas in Indonesia, has suffered from increasing air pollution in the city. The tremendous population growth has created a wide range of urban problems such as the increase of industrial areas and the number of transportation means that lead to the diminished air quality in the area. This study divided Medan into two distinctive areas, namely urban area and suburban area. Air pollution data used for this analysis was taken from Suspended Particulate Matter (SPM) collected by BMKG observation stations in Medan from year 1983 to 2014. According to the trend Analysis of SPM, the area showed an increasing trend of 6.3% in urban area, and of 66% in suburban area. Generally, the increase of SPM that passed the threshold happened in the dry season, which occurs from January until June. The result has displayed there are decreasing of air quality in Medan city, in hope for the policy makers to react accordingly and to plan ways to prevent negative effects of air pollution.